PENINGKATAN KUALITAS PEMBELAJARAN MELALUI KEGIATAN LESSON STUDY DI UNIVERSITAS MAJALENGKA - Erik Santoso (Universitas Majalengka, 2020)
Lesson study is a continuous activity that can be applied through study groups. The purpose of this service is to determine the quality of learning through lesson study activities. The method of implementing the activity is based on the three steps of lesson study activities namely plan, do and see. Planning is the starting point as a key to success in learning. The conclusion from this implementation activity that Lesson study, if it becomes a culture in a learning group, can create a good learning climate. Through ongoing lesson study activities, the quality of learning carried out by educators can improve as well.